ANALISIS STRATEGI MANAJEMEN INVENTARIS DAN PERSEDIAAN DENGAN PERBANDINGAN MODEL EOQ DAN JUST IN TIME DALAM MENINGKATKAN EFISIENSI OPERASIONAL PERUSAHAAN MANUFAKTUR - Simanullang, Renova; Purba, Riska Anggita; Saribu, Ardin Dolok; Sinaga, Sastri; Silaban, Rahmat; Waruwu, Emmuel Prayer; Sitompul, Tanti (Komunitas Manajemen Kompetitif, 2025)
The main objective of this paper is to analyze inventory and supply management strategies by comparing two main approaches, namely Economic Order Quantity (EOQ) and Just In Time (JIT), in an effort to improve the operational efficiency of manufacturing companies. In the context of the industrial revolution and the pressure of globalization, inventory management becomes a key element in supporting the continuity of production and competitiveness of companies. EOQ offers efficiency through calculating optimal order quantities to reduce total inventory costs, while JIT emphasizes the elimination of waste by arranging the arrival of raw materials on time. This paper uses a literature study method to examine inventory management theories and compare the advantages and disadvantages of the main journal with other comparative journals. The results of the study indicate that although EOQ is suitable for environments with stable demand, JIT is superior in dealing with rapid market dynamics, but requires strong infrastructure support and supplier relationships. In addition, this paper also highlights the importance of integrating information technology and human factors in inventory management. The limitations in the main journal lie in the absence of empirical validation and comprehensive system performance evaluation. Therefore, further research is needed with a quantitative approach and field studies to test the effectiveness of the strategy in practice. This paper is expected to be a strategic reference for academics, practitioners, and students in understanding and implementing adaptive and efficient inventory management.